1994
DOI: 10.5271/sjweh.1390
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer and occupational exposures.

Abstract: OBJECTIVES -A hospital-based case-referent study was carried out in Lyon with the purpose of generating hypotheses about the role of occupational exposures to 320 compounds in bladder carcinogenesis. METHODS -Job histories were obtained by questionnaire for 116 cases and 232 reference patients with diseases other than cancer (one referent from the same hospital ward and one from another ward of the same hospital per case); the referents were matched for gender, hospital, age, and nationality. Systematic coding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…This finding is similar to the findings of Kogevinas et al (2003) [6]. It is also compatible with the results of the study by Hours et al (1994) which showed that the risk of bladder cancer among the cases was 2.5 times greater than among the control group (OR = 2.5, 95% CI: 1.2-1.4) [29]. In another study conducted by Colt et al (2004), the risk of bladder cancer among male operators in metal industries, who were involved in welding and molding, was 16.6 times higher than among the control group (OR = 16.6).…”
Section: Discussionsupporting
confidence: 83%
“…This finding is similar to the findings of Kogevinas et al (2003) [6]. It is also compatible with the results of the study by Hours et al (1994) which showed that the risk of bladder cancer among the cases was 2.5 times greater than among the control group (OR = 2.5, 95% CI: 1.2-1.4) [29]. In another study conducted by Colt et al (2004), the risk of bladder cancer among male operators in metal industries, who were involved in welding and molding, was 16.6 times higher than among the control group (OR = 16.6).…”
Section: Discussionsupporting
confidence: 83%
“…Several other occupational exposures that are not industry specific including metal cutting fluids, diesel exhaust, polybrominated biphenyls, and perchloroethylene and other solvents, have been associated, albeit inconsistently, with bladder cancer in some populations. [21][22][23][24][25][26][27] Although the bladder cancer cases in this cohort occurred among workers who held high PFOS exposed jobs, the specific jobs of the cases suggest that other exposures may have been present. The bladder cancer cases worked mostly in maintenance or at the incinerator and wastewater treatment plant.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies had population controls [21,24,27,28,32,33], one [23] both hospital and population controls and the rest had hospital controls [19,20,25,26,[29][30][31]. The diagnoses of the hospital controls by study included: urological controls [19,20,26], osteoarticular, digestive and heart diseases [29], various diseases other than cancer [30], urological and surgical controls [25], various diagnoses excluding urological and heart diseases, cancers of the respiratory system and digestive system [23], and traumas [31]. Controls were individually or frequencymatched to cases on gender, age (within 5 years), and geographic area.…”
Section: Methodsmentioning
confidence: 99%
“…The 14 studies included in the pooled analysis were conducted between 1976 and 1996 and comprised three studies from Germany [19][20][21], two from Spain [22][23][24], Italy [25,26], USA [27,28], and France [14,29,30], and one each from Greece [31], Denmark [32] and Canada [33]. Criteria for inclusion of the studies in the two previous pooled analyses were the availability of detailed information on occupational exposures in studies conducted in European Union countries [17] and of individual exposure estimates to disinfection by-products in studies in Europe or North America [18].…”
Section: Methodsmentioning
confidence: 99%